Penggunaan QR Code pada Proyek Jalan Tol Yogyakarta–Bawen Paket 1 Seksi 1 dan 6 - Muhammad Helmy Ilhamsyah; Dian Herawati; Sudaryono Setyo Nugroho Maximus (Institut Teknologi Garut, 2025)
Digitalization has shifted traditional paradigms into automated systems in safety management, particularly in construction projects. The implementation of QR Code technology in construction safety management systems represents an innovation with the potential to improve verification speed and information accuracy in the field, especially for large-scale infrastructure projects such as the Yogyakarta–Bawen Toll Road, Package 1, Sections 1 and 6. In this study, digitalization is implemented by converting physical documents (e.g., Operation Feasibility Permits and Operator Licenses) into digital formats, which are then linked to QR Codes. This process enables real-time supervision and monitoring, thereby minimizing the risk of workplace accidents and errors in data management. The research method applied is research and development (R&D). During the design stage, the collected data included verification speed, input error rate, and resource efficiency (e.g., reduction of paper usage). The design process also incorporated the integration of sensor technology, augmented reality (AR), and digital twin systems. The proposed system flow diagram illustrates the end-to-end digitalization process, from document conversion to the use of QR Codes as a bridge between the field and the control center. Initial simulation results indicate that the innovation of using QR Codes significantly improves various safety performance indicators. These findings support recommendations for broader adoption in similar infrastructure construction projects to promote efficiency and sustainability programs, such as Adhi Green. This digitalization model is ready to be adopted as a practical solution for enhancing HSE (Health, Safety, and Environment) performance in large-scale projects.